2004
DOI: 10.1046/j.1398-9995.2003.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a 10‐kDa buckwheat molecule reactive to allergic patients’ IgE

Abstract: Molecular cloning experiments indicated that BW10KD as a BW allergen was a member of the 2S-albumin multigene family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 21 publications
(25 reference statements)
2
32
0
Order By: Relevance
“…Shared IgE epitopes are not unique to 19-kD allergen. Marked homology and shared IgE epitopes between 16- and 10-kD BW allergens, which belong to the 2 S storage protein, were also found [14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shared IgE epitopes are not unique to 19-kD allergen. Marked homology and shared IgE epitopes between 16- and 10-kD BW allergens, which belong to the 2 S storage protein, were also found [14]. …”
Section: Discussionmentioning
confidence: 99%
“…The 24-kD BW protein was identified as the β-subunit of 11 S globulin [8,9,10], the 9-kD BW allergen as vicilin [11,12,13] and the 10-kD BW protein as 2 S albumin [14]. Specific IgE (sIgE) antibodies to the 24- and 9-kD allergens can be found in both BW-allergic and asymptomatic subjects, making these allergens poor candidate biomarkers for diagnosis of BW reactivity [13, 15].…”
Section: Introductionmentioning
confidence: 99%
“…2). Matsumoto et al [10] reported that the 10-kDa buckwheat protein, which is identical to the 8-kDa buckwheat allergen, is a member of the 2S albumin multigene family. 2S albumin family proteins have been identified as vacuolar-targeting storage proteins in many plants, and their N-terminal amino acid sequences include signal peptides that are absent in the mature proteins [15,16,17,18].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, 24-, 19-, 16- and 9-kDa proteins have been identified as major buckwheat allergens [7,8,9]. Furthermore, Matsumoto et al [10] have reported a 10-kDa protein and its allergenicity. The 10-kDa protein, which is identical to an 8-kDa buckwheat allergen (Genbank accession No.…”
Section: Introductionmentioning
confidence: 99%
“…The most represented proteins are the so called "storage proteins" and in particular 13S globulins [30]. Several buckwheat proteins are described as being able to bind IgE in allergic patients, and proteins with molecular weight of 9, 16, 19, and 24 kDa are considered major allergens [31][32][33][34][35] (Table 1). It has recently been suggested that sensitization to specific buckwheat allergens would be related to specific symptoms, leading to three different clinical patterns.…”
Section: Buckwheat Allergens and Known Cross-reactivitiesmentioning
confidence: 99%